Security Enhancement of Remote FPGA Devices By a Low Cost Embedded Network Processor - Ali, Qutaiba I.; Lazim, Sahar (Iraqi Journal for Electrical and Electronic Engineering, 2013)
The incredible growth of FPGA capabilities in recent years and the new included features have made them more and more attractive for numerous embedded systems. There is however an important shortcoming concerning security of data and design. Data security implies the protection of the FPGA application in the sense that the data inside the circuit and the data transferred to/from the peripheral circuits during the communication are protected. This paper suggests a new method to support the security of any FPGA platform using network processor technology. Low cost IP2022 UBICOM network processor was used as a security shield in front of any FPGA device. It was supplied with the necessary security methods such as AES ciphering engine, SHA-1, HMAC and an embedded firewall to provide confidentiality, integrity, authenticity, and packets filtering features.